PENGARUH SISTIM TANAM JAJAR LEGOWO TERHADAP HASIL PADI (Oryza sativa L) - Wartapa, Agus; Budijatmo, Hari; Budiono, Ibnu; Susanto, Susanto (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2015)
The title of this research is Influence of row planting system Legowo on productivity. The research aim is to determine the suitable of row planting system Legowo to get the best yield on paddy production. The research was done in BP3K Kalibawang, region Kalibawang, which has altitude 175 m. The experiment started from May to November 2013. The research used field experimental methods with single factorial design that were arranged in randomized complete block design, It was 3 times repeated. The first factor 5 levels are conventional plant (P0), row planting system Legowo 2:1 (P1), row planting system Legowo 3:1 (P2), row planting system Legowo 4:1 (P3), and row planting system Legowo 5:1 (P4). The result showed the method of row planting system Legowo 2:1 give higher yield product on dry grain process, and the best rice quality.